2007
DOI: 10.1016/j.ejcts.2007.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Cost reduction of perioperative coagulation management in cardiac surgery: value of ‘bedside’ thrombelastography (ROTEM)☆

Abstract: Cumulative costs for treatment of perioperative coagulation disorders can be reduced by "bedside" ROTEM analysis to achieve a selective substitution management. Saved costs for blood- and coagulation products clearly outweighed the expenses of ROTEM. Adequate differential coagulation management can therefore be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 24 publications
(28 reference statements)
11
124
0
14
Order By: Relevance
“…The value of ROTEM has also been reported for cardiac surgery and liver transplantations 6,7,17 , where it is particularly important to be able to monitor the coagulation in real time. Unfortunately, such real-time monitoring is not feasible with standard laboratory coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…The value of ROTEM has also been reported for cardiac surgery and liver transplantations 6,7,17 , where it is particularly important to be able to monitor the coagulation in real time. Unfortunately, such real-time monitoring is not feasible with standard laboratory coagulation tests.…”
Section: Discussionmentioning
confidence: 99%
“…A number of retrospective studies have compared the costs of hemotherapy before and after the implementation of POC-based chemotherapeutic algorithms [43][44][45]. Most studies involved cardiothoracic surgery patients and produced conflicting results [43][44][45].…”
Section: Economic Aspectsmentioning
confidence: 99%
“…While Gorlinger et al showed fewer postoperative thrombotic/thromboembolic complications in the POC group compared to the control group, the groups did not differ with respect to perioperative mortality [43][44][45]. In fact, five prospective randomized trials with various lengths of postoperative follow-up have shown no beneficial effect of POC-based coagulation therapy on postoperative mortality [43][44][45]. The blood collection site, method of sampling processing, patient age, and patient gender may significantly affect the results of these tests [46].…”
Section: Limitations Of Pocmentioning
confidence: 99%
“…Other reports have stated the use of different parameters provided by these tests are predictors of both postoperative bleeding and blood product use [143][144][145] . Thrombelastograph Platelet Mapping System has been developed to monitor antiplatelet therapy [146][147][148][149] .…”
Section: Viscoelastic Methodsmentioning
confidence: 99%